1998
DOI: 10.1136/jnnp.64.1.37
|View full text |Cite
|
Sign up to set email alerts
|

A population study of apoE genotype at the age of 85: relation to dementia, cerebrovascular disease, and mortality

Abstract: Objectives-To study the association of apoE genotypes with dementia and cerebrovascular disorders in a population based sample of 85 year old people. Methods-A representative sample of 85 year old people (303 non-demented, 109 demented) were given a neuropsychiatric and a medical examination and head CT. The apoE isoforms were determined. Dementia was diagnosed according to DSM-III-R. Results-At the age of 85, carriers of the apoE 4 allele had an increased odds ratio (OR) for dementia (1.9; p<0.01) and its sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
4
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 51 publications
10
75
4
1
Order By: Relevance
“…[23][24][25][26][27][28] In the present longitudinal study, the APOE ⑀4 allele did not significantly increase the risk of dementia with stroke, in disagreement with a previous casecontrol study. 11 It has been shown that the APOE ⑀4 allele is related to early death, 52 especially in those with good cognition.…”
Section: Apoe ⑀4 Increases the Risk Of Dementia Without Stroke But Nocontrasting
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] In the present longitudinal study, the APOE ⑀4 allele did not significantly increase the risk of dementia with stroke, in disagreement with a previous casecontrol study. 11 It has been shown that the APOE ⑀4 allele is related to early death, 52 especially in those with good cognition.…”
Section: Apoe ⑀4 Increases the Risk Of Dementia Without Stroke But Nocontrasting
confidence: 99%
“…11,17,19 -28 In some studies, the APOE ⑀4 allele has been associated with increased risk of vascular dementia, 11,17,20 -22 but other studies have failed to confirm this association. [23][24][25][26][27][28] Finally, an ethnic variation of the APOE effect on dementia has been reported. The APOE ⑀4 allele is not a significant risk factor for AD among blacks and Hispanics.…”
mentioning
confidence: 93%
“…14 -36,48 Eleven compared the numbers of individuals in lower and upper WMH grades between genotype groups ( Figure 1A), 14,16,17,22,23,25,29,30,33 3 compared mean grade ( Figure 1B), 15,21,24 and 4 compared mean volume ( Figure 1C). 20,28,34 Random-effects meta-analyses comparing 4ϩ with 4Ϫ genotypes found no evidence of association between APOE and WMH (graded WMH dichotomous pooled OR, 0.97; 95% CI, 0.78 -1.21; graded WMH continuous pooled standardized mean difference: 0.30, 95% CI, Ϫ0.02-0.62; WMH volume pooled standardized mean difference: 0.15, 95%CI Ϫ0.04 to 0.33).…”
Section: Resultsmentioning
confidence: 99%
“…Although APOE genotype was not considered, data from the Cache County Study (30) support the findings of increased stroke-associated risk of AD in the presence of vascular risk factors. The presence of APOE-ε4 has been shown to be a risk factor for dementia with stroke in two population-based casecontrol studies (31,32).…”
Section: Discussionmentioning
confidence: 99%